Naturally Occurring Steroidal Saponins as Potential Anticancer Agents: Current Developments and Mechanisms of Action - Zou, Yulin (Current Topics in Medicinal Chemistry, 2022)
Cancer is claimed as a prevalent cause of mortality throughout the world. Conventional chemotherapy plays a pivotal role in the treatment of cancers, but multidrug resistance has already become one of the major impediments to efficacious cancer therapy, creating a great demand for the development of novel anticancer drugs. Steroidal saponins, abundantly found in nature, possess extensive structural variability, and some naturally occurring steroidal saponins exhibit profound anticancer properties through a variety of pathways. Hence, naturally occurring steroidal saponins are powerful lead compounds/candidates in the development of novel therapeutic agents. This review article described the recent progress of naturally occurring steroidal saponins as potential anticancer agents, and the mechanisms of action were also discussed, covering articles published between 2017 and 2021.
Keywords: Natural products